First Year Experience in Assisted Reproductive Technology (ART) Services at IIUM Kuantan - Murad Zainuddin, Assoc. Prof. Dr Ahmad; R, Roszaman; YW, Azantee; MY, Hayati; MA, Norsina; K, Siti (IIUM Medical Journal Malaysia, 2013)
Introduction: To analyze the ART outcome and factors associated with successful ART treatment for infertile couples in a newly set up medical university IVF centre. Methods: A six-month cohort study of patients undergoing their first assisted reproductive technique cycle was conducted at IIUM fertility centre, Kuantan (from 15th June until 31st Dec 2009). Outcome measures include clinical pregnancy rate, ongoing pregnancy rate, take home baby rate and complications rate. Results: Fifty-five first cycles of IVF/ICSI were studied. Mean embryo per transfer was 2.1±0.8. Four patients were pregnant (23.5%) from a single embryo transfer (SET). Clinical pregnancy rate was 30.9% (17/55). Ongoing pregnancy rate was 23.6% (13/55) and take home baby rate was 21.8% (12/55). There was only one twin pregnancy. Nine patients (16.4%) had OHSS whereby 77.8% were mild and 22.2% were moderate. Conclusion: Take home baby rate at the IIUM fertility centre is comparable to most established ART centres in Malaysia considering that this is only the first year of operation.